The Mechanics of Modernity in Europe and East Asia - Ringmar, Erik (Routledge Explorations in Economic History, 2005)
Why, from the eighteenth century onwards, did some countries embark on a path of sustained economic growth, while others stagnated? This text looks at the kind of institutions that are required in order for change to take place, and Ringmar concludes that for sustained development to be possible, change must be institutionalized. Taking a global view, Ringmar investigates the implications of his conclusion on issues facing the developing world today.